Celestial Diglossia and the Moral Clock: Ethno Linguistic Encoding of Cosmology and Social Hierarchy in Ethiopian Life Cycle Ritual Discourse - Muhammad Ridwan; Belay Sitotaw Goshu; Arifulhak Aceh (LingLit Journal Scientific Journal for Linguistics and Literature, 2026)
Ethiopian life‑cycle rituals have been extensively documented, yet the specific linguistic mechanisms that encode cosmology and social hierarchy remain undertheorised. Existing studies treat language as a transparent medium rather than a constitutive force. This article introduces two novel concepts, celestial diglossia (stratified access to astronomical registers) and the moral clock (celestial events that license ritual speech)—to explain how Oromo, Amhara, and Gedeo ritual discourse re‑classifies initiates across birth, initiation, marriage, and death. Twelve months of participant observation, 85 interviews with ritual specialists (Hayyu, Qallu, priests, Zār leaders), and audio‑recorded speech events (marriage negotiations, Dhibaayyuu vows, Zār healing sessions) were analysed using discourse analysis and ethnographic semantics. Celestial diglossia parallels the Ge‛ez‑Amharic split, creating an epistemic hierarchy where priests control constellation names (e.g., Bakkalcha/Pleiades) and heliacal calculations. The moral clock exemplified by Bakkalcha’s rising—periodically licenses Mekdes (loyal reproach), transforming taboo direct criticism into a “face gift.” This temporary inversion reinforces rather than subverts hierarchy. In Gadaa transitions, the new Abbaa Gadaa cannot pronounce judgement formulas until Bakkalcha’s first sighting. Eclipses suspend all ritual speech, proving the clock’s regulatory coherence. Ethiopian ritual discourse accomplishes a triple transformation (biological→social→cosmic) through linguistic encoding, not mere symbolism. Age‑grade progression is mapped directly onto observable celestial events. Linguistic anthropology must integrate astronomical time as a performative dimension. Future research should examine southern Ethiopian groups (Sidama, Konso) and the impact of Orthodox Christianity on contemporary ritual registers.